Pengaruh Kualitas Produk, Citra Merek, dan Kepercayaan Merek Terhadap Loyalitas Pelanggan - Mhd Rizki Hidayat; Elvina; Yanto Zelibu (Journal of Trends Economics and Accounting Research, 2025)
This study aims to determine the effect of product quality on customer loyalty partially. To determine the effect of brand image on loyalty partially. To determine the effect of product quality on customer loyalty partially. To determine the effect of product quality, brand image and trust on customer loyalty simultaneously. The analysis method in this study is to use primary data in the form of distributing questionnaires. The population in this study were Dayasa Coffee Rantauprapat customers with a sample of 96 respondents. Data analysis used SPSS Version 23, through validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression, T tests, F tests, and coefficients of determination. The results showed that the influence of product quality, brand image and brand trust partially had a significant effect on customer loyalty. In addition, the results of the study also show that product quality, brand image and brand trust have a simultaneous effect on customer loyalty, because the brand image variable has the most value on customer loyalty of Dayasa Coffee Rantauprapat, so researchers are more concerned with improving the taste of Dayasa Coffee Rantauprapat's flagship product to better enhance an attractive brand image. Researchers are also expected to expand the brand image variable and can add variables that are not in this study such as Price, Beauty Influencer, Live Streaming, so that in the future they can achieve customer loyalty.